Business librarians and new academic program review. Issue 2 (2nd April 2016) - Wu, Kerry; Senior, Heidi
ABSTRACT: The article aims to examine the role business librarians play in the new academic program proposal process on university and college campuses. Results of a nationwide online survey showed that current practices in this critical area varied. Although more than 60% of the respondents thought that librarians should play a part in the proposal process, more than 65% of them indicated that they were never involved. Among those that participated, the levels and outcomes also differed greatly. The authors held in-depth interviews with survey participants reporting higher-than-average involvement to find out about their strategies for success.